The representation of animals at Alain MABANCKOU: Literary (Cahiers Africains de rhétorique, 2025)
We propose to study the representation of animals in the novels of Alain Mabanckou. They are of various kinds and constitute the very foundation of literary texts. Their recurrence and persistence allow the astute reader to observe the bad behavior of man in society. Certain animals relate to fables or ancient mythology, to the protective totems of an individual, a clan, a family; others refer to wild and domestic bestiaries. They all serve to depict the vices of man, to correct them. The thematic method makes it possible to highlight the power of obsession of each animal, to identify its meaning.